Implementasi Aplikasi Keberangkatan Pelaut Berbasis Web Menggunakan Metode AHP (Analytic Hierarchy Process) - Teguh Triatmojo; Muhammad Rifqi (Computer Engineering Departement, Universitas Komputer Indonesia, 2022)
ABSTRACT – The development of information systems nowadays has shown an interesting phenomenon. Various kinds of education, government, agencies, many more use technology to help improve performance, but unfortunately not all agencies take advantage of existing technology, call it FOS Management, in making work reports for seafarers FOS Management Service in Jakarta, currently it is still carried out continuously. manual via cell phone or cell phone. For this reason, researchers made a web-based seafarer contract application using the ahp method, the expected contribution with this application can make it easier for ship crews to determine departures from the departure date, end date and the like more effectively and efficiently and ease the work reports of seafarers who initially is manual, becomes completely digital. With the weighting of the Ahp (analytic hierarchy process) method, the problem with selecting prospective seafarers to be dispatched can be resolved.